Using Generalized Linear Model to Determine the Impact of Oil Price Fluctuations on the Egyptian Public Budget - Alhendawya, Hamdy Ahmad Aly; Mostafa, Mohammed Galal Abdallah; Elkananib, Sozan Galal; Zakic, Neveen Mohsen Ahamed; Selmeya, Mousa Gowfal (International Journal of Energy Economics and Policy, 2023)
Oil is regarded as one of the most significant energy sources in the world due to the enormous impacts it has on the level of the economy as a whole in both developing and developed countries and for both producing and importing countries. so, this study aims to know the effects of fluctuations in oil prices on the Egyptian public budget during the period from 2000 to 2022. For this purpose, the study used the GLM(Generalized linear Model) model, which is one of the first studies to use this model in economics. The study concluded that oil price fluctuations negatively affect the public budget, which means that there is a positive relationship between oil price fluctuations and the general budget deficit in Egypt as a result of Egypt being one of its importing countries. Therefore, the rise in oil prices leads to an increase in the public budget deficit, and its low prices may contribute to a decrease in this deficit.